Audit Committee Characteristics and Factors Related to Earnings Management - Nelwan, Melinda Lydia (JBE (Journal of Business and Economics); Volume 10 No.1, 2011 JBE UNKLAB, 2011)
The pervasiveness of corporate governance cannot be separated with the existence of audit committee. It is expected that audit committee would be able to mitigate the agency costs caused by the asymmetric of information, thus aligning the interests of management and shareholders.  However, there is no such a guarantee that the likelihood of management to act according to their interest would be completely eliminated. Hence, there is still a tendency for the management to expropriate the resources of the corporation and use the private information they possessed to manipulate earnings. This article indentifies several characteristics of audit committee in determining their effectiveness to perform monitoring role and what factors of the characteristics are related to earnings management practices. The extant literatures show that several characteristics effectively reduce the earnings management practices, while the others do not have significant evidence in alleviating these practices.